Penyusunan Norma EPPS Berdasarkan Tingkat Pendidikan SMA, Perguruan Tinggi dan Rentang Usia Dewasa Awal - Lisa Imelia Satyawan; Heliany Kiswantomo (Humanitas (Jurnal Psikologi), 2017)
This research is to develop new EPPSâ€™ norms. EPPS were widely used to measure human personality, in various settings, such as education, clinical and industries. The existing norms used today, was constructed at 1960, so itâ€™s important to construct new norms. EPPS Â is one of the personality tests that measure 15 needs from Murray, there are need of achievement, deference, order, exhibition, autonomy, affiliation, intraception, succorance, dominance, abasement, nurturance, change, endurance, heterosexual and aggression. The test formâ€™s is forced choiced, the subjects were asked to choose one of the two statements that suitable Â with them. This is a descriptive survey study, with 1646 respondents from various high school in Indonesia, and college, so norms will be able to represent adolescents and early adulthood in Indonesia. Data obtained were Â analyzed with descriptive statistics. The results of this study are inter-norm, based on age and level of education. These norms can be used by psychologists to Â describe Â personality, inÂ variety settings. Â Keywords: need, norms, EPPS